Pengaruh Lingkungan Kerja, Kompetensi, Dan Pengembangan Karir Terhadap Kinerja Pegawai Pada Bank BTN KC Denpasar - Cahyani, Ariesta Gige Setia; Wijayanti, Dewie Tri; Witjaksono, Andre Dwijanto (Community Engagement and Emergence Journal (CEEJ), 2025)
This study aims to analyze the influence of career development, work environment, and competence on employee performance at Bank BTN Denpasar Branch Office. The phenomenon of lower performance and the increasing demand for competencies in the banking sector underscore the importance of this research, particularly in the context of regional banking. A quantitative method with a survey approach was employed. The respondents consisted of 115 permanent employees of Bank BTN Denpasar Branch, selected using a saturated sampling technique. Data were collected through questionnaires using a Likert scale. The data were then analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine both the simultaneous and partial effects of the independent variables on the dependent variable. The results indicate that career development has a strong and significant direct influence on employee performance. In contrast, the direct effects of work environment and competence on performance were not statistically significant; however, both variables contribute indirectly through their positive influence on career development. These findings suggest that to foster optimal employee performance, organizations need to focus not only on improving the work environment and building employee competencies but also on ensuring clear and structured career development pathways.